Book Review: Edward Shizha and Lamine Diallo, Africa in the Age of Globalisation: Perceptions, Misperceptions and Realities. Issue 1 (January 2017) - Ansari, Khalid
Edward Shizha and Lamine Diallo, Africa in the Age of Globalisation: Perceptions, Misperceptions and Realities, Ashgate, Surrey, England, 2015, 277 pp., $119 (Hardcover), ISBN: 9781472436696.